Factors related to leftovers of Inpatiens at Anutapura Public Hospital, Palu City - Izzah, Nurul (Preventif : Jurnal Kesehatan Masyarakat, 2022)
Leftovers are the percentage of food that is not eaten or eaten by the patient and is disposed of as waste. The challenge in providing food in hospitals that must be followed up immediately is that there are still a lot of leftovers from the patient's food. Leftover can be caused by various factors. This research aims to find out the factors related to food waste. This type of research was analytical observational with a quantitative approach and used a cross-sectional research design. The population of this research was all hospitalized patients who received food without a diet in the form of soft or ordinary hospital standards. The sample totaled 50 respondents which were selected through the accidental sampling technique. The data obtained were analyzed using the Chi-square test. The results of the research show that there is a relationship between food taste (p<0.05), food menu (p<0.05), and length of stay (p<0.05) with food waste of inpatients at Anutapura Public Hospital, Palu City. Respondents assessments of taste and food menus vary. When sick, the sense of taste of a tongue tastes bitter, bland, and can't taste the taste of each type of food so that it affects whether or not there is a lot of leftover food. Ingredients and food menus that are served several times at each meal and boredom during hospitalization can make the response reluctant to finish the food served